Fabrication and characterization of Pb-Ge-Te nanocrystals and thin films as a potential material for ferroelectric applications - El-Khodary, Asmaa Mohammed (AUC Knowledge Fountain, 2019)
Recent trends of technology require reliable memory devices in terms of large capacity, bandwidth, and high performance along with low power consumption and cost to be compatible with scaling computing systems size. Currently, charge based memories such as dynamic random access memory (DRAM) face some issues in density scaling due to the high power needed to refresh the memory cell in order to keep its contents, which leads to a high production cost [1]. Non-volatile ferroelectric random access memory (NVFRAM) is considered a promising solution since it tackles the problem of high power consumption for refreshing cycles, being non-volatile, in addition to their nanosecond switching speed and capability of processing massive amounts of data similar to DRAM and flash memory[2]. Lead zirconate titanate or PZT (Pb(ZrₓTi₁₋ₓ)O₃) capacitors are widely used in FRAM technology due to their excellent ferroelectric properties, however, they show degradation of polarization with increasing switching cycles owing to domain locking caused by the large amount of oxygen vacancies. Attempts to overcome the fatigue behavior of PZT were to use oxide electrodes instead of metallic ones, which adversely affect other properties of the memory cell- for instance leakage and data retention[3, 4]. Recently, doped binary crystals such as Ge doped- PbTe have been highlighted, due to their simple structure as well as ferroelectric properties, as a candidate for FRAM manufacturing[5]. The class of IV-VI semiconductor nanocrystals, among them germanium and lead tellurides, have been studied extensively over the past few decades due to their outstanding physical properties. They have a great potential for mid-infrared optoelectronic devices, such as photon detectors and laser emitters, in addition to energy conversion systems, such as solar cells, owing to their narrow band gap energy [6, 7]. Their high thermoelectric figure of merit makes them excellent for thermoelectric device applications. Moreover, their ability to undergo a structural ferroelectric phase transition, together with their reversible phase change from amorphous to crystalline state qualifies them for ferroelectric random access memory (FRAM) and phase change memory (PCM) applications. The present study is aiming to investigate the structural, optical, electrical, and ferroelectric properties of Pb₅₀₋ₓGeₓTe₅₀ (x = 15, 20, 25, 30 at.%) nanocrystalline alloys, with a deep focus on increasing the ferroelectric phase transition temperature to overcome the first barrier of applying them to memory storage devices. This dissertation is composed of five chapters, The 1st chapter “Introduction” provides a brief explanation of the current challenges facing memory systems with a special focus on FRAM as a potential solution, along with presenting the main properties of IV- tellurides. The 2nd chapter “Literature Review” includes the previous work reported for the binary alloys PbTe and GeTe together with the ternary system Pb-Ge-Te. The 3rd chapter “Theoretical Background” introduces briefly the main theoretical models applied for crystalline semiconductors and the concept of ferroelectricity. The 4th chapter “Materials and Methods” collects the experimental techniques used in the current investigation. The 5th chapter “Results and Discussion” reports and analyzes the results of this experimental study, in addition to concluding the most important outcomes with proposing some future research scopes.